Teaching English to Young Learners: the Complexity of Reality - Aprilian Ria Adisti; Issy Yuliasri; Rudi Hartono; Sri Wuli Fitriati (Universitas Negeri Semarang, 2021)
The education system in Indonesia is overgrowing along with globalization. Since English becomes the world's lingua franca, Indonesia has implemented Teaching English to Young Learner (TEYL) as the local content subject for the last two decades. This study is a descriptive qualitative study that aims to expose the realization of TEYL in kindergarten. The data collection instruments are a survey and Focus Group Discussion (FGD). A survey was conducted on 50 principals and teachers from 25 kindergartens in Salatiga, Central Java, in February 2021. The result showed that 96 percent of respondents considered introducing English as a foreign language in an early childhood education highly needed. Furthermore, the majority (100 percent) of the respondents' schools teach English as an extracurricular subject. On the aspect of teacher education background, it was found that only 14 percent of teachers in TEYL graduated from the English education department. Then, only 48 percent of respondents argued that the media in their school had already supported the TEYL program. Lastly, only 30 percent perceived that the TEYL program had been integrated with the early childhood education curriculum. In addition, the FGD also exposed the complexity of reality in TEYL. Finally, it can be concluded that in realizing an ideal TEYL is still needed many improvements in pedagogy, quality of teachers, good resources, curriculum, and media based on needs analysis.